THAI’S GOVERNMENT POLICY TOWARDS ROHINGYA REFUGEES - Musreefudeen (MIHI UMY, 2016)
ABSTRACT This Postgraduate thesis tried to describe Thai’s government policy towards Rohingya refugees. The issue of refugee’s influx to Thailand actually that happened for long time become a famous issue in January 2013 when immigration police arrested more than 800 migrants near the border town of Pedang Besar in the town of Sadao, Songkla province and in May 2015 the Police discovered 32 mass graves at Padang Besar border of Songkla province. Thai’s government manage act to Rohingya refugees are 2 divided into processes first Thai’s government faltering immigration system to classify of Rohingya refugees depend on the status in three categories such as Illegal Immigrant, Migrant worker and human trafficking, Second Resettlement to the third countries such as Malaysia, Indonesia, United State, Canada and Australia. This thesis is using descriptive method with qualitative approach. Collecting data technique library research, journals, books, interview and other relevant data to the thesis.